2012
DOI: 10.1051/mbcb/2012013
|View full text |Cite
|
Sign up to set email alerts
|

Exostoses buccales : revue de la littérature

Abstract: Résumé -Les exostoses buccales sont des tumeurs osseuses bénignes des maxillaires qui se manifestent par des excroissances osseuses exophytiques. L'objectif de cette étude était d'effectuer une revue de la littérature sur ce sujet. Les données épidémiologiques, remontant pour certaines à plus d'un siècle, révèlent de grandes disparités selon les populations et les auteurs. La fréquence et la répartition des exostoses buccales diffèrent d'une population à l'autre. La susceptibilité génétique, les forces mastica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(22 citation statements)
references
References 66 publications
0
14
0
1
Order By: Relevance
“…On the contrary, several authors have cited that environmental factors are likely to promote oral exostoses. Although not clearly identified, masticatory hyperactivity and para-functions appear to be the main factors, with diet (unsaturated fatty acids and calcium) to a lesser extent [1,4,7].…”
Section: Etiological Hypothesesmentioning
confidence: 89%
See 3 more Smart Citations
“…On the contrary, several authors have cited that environmental factors are likely to promote oral exostoses. Although not clearly identified, masticatory hyperactivity and para-functions appear to be the main factors, with diet (unsaturated fatty acids and calcium) to a lesser extent [1,4,7].…”
Section: Etiological Hypothesesmentioning
confidence: 89%
“…The average prevalence of palatal tori seems to be 20-40% with significant topographical disparities. Most authors have observed a predominance of palatal tori in women as well as a larger average size [1][2][3][4].…”
Section: Epidemiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Le TP est le plus souvent rencontré chez les femmes [1][2][3][4][5][6] entre la 3 e et la 4 e décade [1]. Aux États-Unis, il est plus fréquemment rapporté chez les Caucasiens par rapport aux Afro-Américains [1].…”
Section: éPidémiologieunclassified